Catch Fish Profile at Amagarapati Fish Landing Port, East Flores Regency, East Nusa Tenggara Province - Idrus, Muhamad Amril; Nandito, Krisnawan; Sari, Annisa Megia (Journal Omni-Akuatika, 2022)
East Nusa Tenggara (NTT) Province has many business potentials in the marine and fisheries sectors, especially fish as a commodity. East Flores District is one of the fish landing centers for fishing vessels in the East Nusa Tenggara Province. The objective of this study was to determine the activities of fishing vessels and to find out the catches that have been landed at Amagarapati Fish Landing Port. The location of this study was determined by purposive sampling, while the research location was carried out at Amagarapati Fish Landing Port. This research was conducted in July-October 2021. A descriptive survey was chosen as the data collection method by conducting direct observations in the field such as giving interviews and distributing questionnaires to the fishermen and Amagarapati Fish Landing Port’s employees. The results of this study showed that fishing activities at Amagarapati Fish Landing Port were running normally as usual even though Implementation of restrictions on community activities (PPKM) was implemented in East Flores Regency, the fish caught were dominated by Skipjack, Mackerel Tuna, Tuna, Mackerel Scad, and Atlantic Menhaden. There was an obstacle in the decline in fish prices due to the decline in people's purchasing power, tuna exports to the United States experienced a decline due to the lockdown destination countries. The catch that landed at Amagarapati Fish Landing Port 2,527.5 Tons of catches were reduced due to bad weather, the availability of fish bait for pole and line vessels was limited so that it hampered fishing activities.Keywords: Amagarapati Fish Landing Port, Fish Catch, and Fishing Vessels